Criteria of Bad Debt at National Banks That Have an Implication for Corruption - Rudhy Parhusip (Universitas Negeri Semarang, 2019)
Banking is closely related to risk management as seen in Bank Indonesia Regulation number 11/25/2009 concerning Amendments to Bank Indonesia Regulation (PBI) Number: 5/8/2003 concerning Application of Risk Management for Commercial Banks. In Article 1 number 4 PBI 11/25/2009, explained risk is the potential loss due to the occurrence of certain events. The types of risks that might occur, are described in Article 4 PBI: 11/25/2009 namely Credit Risk, Market Risk, Liquidity Risk, Operational Risk, Legal Risk, Reputation Risk, Strategic Risk and Compliance Risk, but law enforcement officials cannot distinguish whether a state loss is the result of a Business Judgment Rule (BJR) or indeed an illegal act, focus on a state financial loss.